OPTIMALISASI KINERJA TIM DAN PROFESIONALISME SOP UMKM: TRANSFORMASI SUMBER DAYA MANUSIA DI YAYASAN AL-ASHRIYYAH NURUL IMAN BOGOR - Ahmad, Ahmad; Susita, Dewi; Sariwulan, Tuty; Wijaya, Andreas; Kurniawan, Erfan (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
MSMEs play a vital role in national economic development through economic growth, job creation, and equitable distribution of benefits. The aim of this community service is to enhance the human resource competencies of MSMEs within the Islamic Boarding School in a sustainable manner. The role of the santri as managers requires both theoretical guidance and practical mentoring in developing operational procedures that meet their needs, focusing on enhancing the required competencies. The method applied, involving interactive training and direct practice by 50 managers, demonstrates high enthusiasm. Thus, community service through training for santri to enhance their competencies is crucial for the future. The outcome of these activities includes fostering self-evaluation among santri to improve their competencies through work standards and workflows. Additionally, the unique aspect of this initiative involves enhancing their understanding of building strong teams and developing sustainable business strategies through the managers' role as organizational drivers.